The compositions of biomarkers and macerals in the first member of the Shahejie Formation in the Liaodong Bay subbasin, Bohai Bay Basin: Implications for biological sources and seawater incursions - Wang, Ning; Xu, Yaohui; Li, Wei; Wang, Feilong; Chen, Guo; Liu, Yan; Cheng, Rujiao; Liu, Huaqiu (Journal of petroleum science & engineering, 2022)
Seven mudstone/shale core samples were collected from the first member of the Shahejie Formation (E2s1) in this study, which is considered as a potential source rock in the Liaodong Bay subbasin. The biological sources and sedimentary environments of the E2s1 source rocks were studied based on the analyses of organic geochemistry and organic petrology. The results indicate that E2s1 source rocks were deposited in a lacustrine environment with relatively high salinity, which caused the stratification of water body and anoxic bottom conditions. The abundant and stable presence of regular steranes, dinosteranes, 4α-methyl-24-ethylcholestanes, 24-norcholestanes, 24-n-propylcholestanes, hopanes, 2α-methylhopanes, and 3β-methylhopanes in the studied samples indicate that dinoflagellates, diatoms, pelagophyceae, cyanobacteria, rhizobiales and aerobic methanotrophs were the main biological sources of the E2s1. Among them, dinoflagellates are closely related to the formation of organic-rich E2s1 source rocks, which is supported by the positive correlation between TOC or HIvalues and 4α-methyl-24-ethylcholestane (biomarker of dinoflagellates) contents. Trace amounts of terrestrial higher plant biomarkers in the studied samples indicated that their contributions to organic matter were limited. This is consistent with the abundance of lamalginite and mineral-bituminous groundmasses observed in the E2s1 samples under optical micrographs. Widely occurring marine incursion events in the Eocene in the Bohai Bay Basin may have also occurred during the deposition of the E2s1 in the Liaodong Bay subbasin, supported by the presence of a typical marine pelagophyceae biomarker (24-n-propylcholestane). •Biological sources of E2s1 from the Liaodong Bay subbasin have been discussed.•The formation of the E2s1 source rocks may be related to a marine incursion event.•Dinoflagellate play an important role in the formation of the E2s1 source rocks.